2021
DOI: 10.3389/fnut.2021.775515
|View full text |Cite
|
Sign up to set email alerts
|

Orange Juice Attenuates Circulating miR-150-5p, miR-25-3p, and miR-451a in Healthy Smokers: A Randomized Crossover Study

Abstract: Introduction: Tobacco smoke is associated with oxidative and inflammatory pathways, increasing the risk of chronic-degenerative diseases. Our goal was to evaluate the effects of acute “Pera” and “Moro” orange juice consumption on inflammatory processes and oxidative stress in microRNA (miRNA) expression in plasma from healthy smokers.Methods: This was a randomized crossover study that included healthy smokers over 18 years old. Blood samples were collected before and 11 h after beverage ingestion. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…These 5 miRNAs regulate 52 proteins identified as differently expressed in our study. Other 6 miRNAs (miR-150-5p, miR-375, miR-130b-3p, miR-25-3p, miR-424-5p, and miR-144-3p) were previously reported [68][69][70] as modulated by OJ consumption, which directly regulate 21 differentially expressed proteins in our study. Taken together, bioinformatic analyses evidenced the potential effect of OJ consumption on several metabolic processes and shed light on four pathways (focal adhesion, HIF-1 signaling pathway, phagosome, and PI3K-Akt signaling pathway), which were identified as containing the higher numbers of overlapped proteins considering both datasets.…”
Section: Food and Function Papersupporting
confidence: 62%
“…These 5 miRNAs regulate 52 proteins identified as differently expressed in our study. Other 6 miRNAs (miR-150-5p, miR-375, miR-130b-3p, miR-25-3p, miR-424-5p, and miR-144-3p) were previously reported [68][69][70] as modulated by OJ consumption, which directly regulate 21 differentially expressed proteins in our study. Taken together, bioinformatic analyses evidenced the potential effect of OJ consumption on several metabolic processes and shed light on four pathways (focal adhesion, HIF-1 signaling pathway, phagosome, and PI3K-Akt signaling pathway), which were identified as containing the higher numbers of overlapped proteins considering both datasets.…”
Section: Food and Function Papersupporting
confidence: 62%
“…found that plasma levels of circulating miR‐150‐5p were higher following tobacco intake via cigarette smoking. 105 Bioinformatic analysis was used to identify oxidative stress, and the ErbB signaling pathway was found to be among the enriched pathways regulated by genes targeted by miRNAs. This pathway has previously been implicated in numerous smoking‐related cardiovascular diseases due.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have investigated the benefits of blood orange juice intake, especially of the Moro variety ( Dorna et al, 2021 ; Nishioka et al, 2021 ; Ribeiro et al, 2021 ; Briskey et al, 2022 ; Santana et al, 2022 ; Capetini et al, 2023 ). However, the effects of MOJ on the gut microbiota profiles have not been investigated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified novel polymorphisms ( Fraga et al, 2022 ) and microRNAs ( Dorna et al, 2021 ; Quintanilha et al, 2022 ; Capetini et al, 2023 ), which regulate cellular processes and mechanisms that are associated with the benefits of orange juice intake. This is one of the few studies that has evaluated the effects of MOJ on the gut microbiota composition and is the first study to report the correlation between the gut microbiota composition and the cardiometabolic biomarkers.…”
Section: Discussionmentioning
confidence: 99%